Physico-chemical characteristics and microbial profile of sapota var. jantung. - Abdul Karim, Mohamad Nordin; Abu Bakar, Fatimah (1988)
Studies carried out using tagged fruits showed that sapota of jantung variety attained maturity after six months from fruit set. The weight, length, width and volume of the fruit increase until harvest slowing between six and seven months. This coincides with the colour changes of the pulp and pip. The fruits firmness decreases towards maturity. Moisture and tannin content reach maximum level between fifth and sixth month whereby the total titratable acidity decreases gradually. Total soluble solid increases throughout the fruit development. Fruits harvested after six months have a low rate of respiration. The length and width of the fruit are greatly influenced by age and can be used as an index of maturity. The normal microflora of sapota consist of bacteria, moulds and yeasts. During ripening the population of bacteria decreases with an increase in the yeasts population. In contrast, the number of moulds remain constant throughout. The genera of bacteria found include Bacillus spp, Erwinia spp and Micrococcus sp. Moulds belong to genera Aspegillus spp, geotrichum spp and Mucor spp whilst yeasts include Rhodotorula spp, Brettamonyces spp and Pichia spp.